2011
DOI: 10.1080/03601234.2011.589309
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide risk assessment: A study on inhalation and dermal exposure to 2,4-D and paraquat among Malaysian paddy farmers

Abstract: A cross-section analytical study was conducted to evaluate the risk of pesticide exposure to those applying the Class II pesticides 2,4-D and paraquat in the paddy-growing areas of Kerian, Perak, Malaysia. It investigated the influence of weather on exposure as well as documented health problems commonly related to pesticide exposure. Potential inhalation and dermal exposure for 140 paddy farmers (handlers of pesticides) were assessed. Results showed that while temperature and humidity affected exposure, winds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 6 publications
2
48
0
2
Order By: Relevance
“…Toxicological studies have shown that different mechanisms could be associated with various adverse respiratory outcomes, including asthma. Respiratory absorption of paraquat is high in occupational exposure 17) . It destroys cell membranes and causes the formation of superoxide free radicals which are responsible for the pesticide's toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological studies have shown that different mechanisms could be associated with various adverse respiratory outcomes, including asthma. Respiratory absorption of paraquat is high in occupational exposure 17) . It destroys cell membranes and causes the formation of superoxide free radicals which are responsible for the pesticide's toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The United States Environmental Protection Agency suggests that more than 25% of regular housekeeping detergents used are hazardous to health 37,62. Many cleaners also lack chemical training 63. Negative loading observed on the outside air intake relates to AHU design; in Asia, the main source of pollutants is sometimes not taken into consideration in the design/plan of AHU.…”
Section: Discussionmentioning
confidence: 99%
“…The Islamic banks in Jordan have no access to the advantages and benefits available in social responsibility, under this condition, the Islamic banks can't reach to the optimal size of market share and profits margins , so the potential threats and idle opportunities may facing such banks on the long run will be increased. For example, study of Bharuddin et al, (2014) indicates the positive relationship between social responsibility, growth and profits. Group of researchers Chung, Yu, Choi and Shin (2015) they found that low rate of customer satisfaction will decrease the customers' loyalty as well, and both of them are important determinants of growth and profit.…”
Section: Discussion Implications and Recommendations 81 Findings DImentioning
confidence: 99%